Optimizing Link and Match Strategy between PTKN and the Industrial World to Improve Graduates' Job Readiness - Anis Ulil Hidayati (AMUYA: JOURNAL OF MANAGEMENT, 2026)
This policy paper examines the structural challenges faced by State Religious Higher Education (PTKN) in Indonesia in the form of a high skills mismatch between graduate competencies and the skills demands of the Business and Industrial World (DUDI). This phenomenon is exacerbated by the PTKN curriculum which tends to be normatively academically oriented and not fully responsive to technological developments and Industry 4.0, as well as the low exposure of students to industrial experience due to the absence of an adequately integrated Structured Internship Program (SIP). This has an impact on the low competitiveness and employment absorption of graduates. Methodology: This policy paper uses a qualitative descriptive policy analysis approach to identify the root of the problem and formulate regulatory policy recommendations. Determination of policy problem priorities is carried out through the Urgency, Seriousness, Growth (USG) Analysis, which places the problem of competency mismatch as the main priority with the highest total score (15). Furthermore, five policy alternatives are evaluated using the William N. Dunn Policy Evaluation Model based on the criteria of Effectiveness, Efficiency, Adequacy, and Responsiveness. Results and Recommendations: Based on Dunn's evaluation, the most superior policy alternative is the Issuance of the Decree of the Director General of Islamic Education concerning National Standards for Cooperation between PTKN and DUDI with a total score of 19. This regulation is recommended because it has the highest potential in creating standardized and systemic partnership governance, overcoming institutional fragmentation, and becoming an operational basis for PTKN to integrate Outcome-Based Education (OBE)-based curriculum and requiring structured industrial practice experience, thus significantly increasing the relevance of graduates to the needs of the modern job market.